Effect of fibre topology on hygro-mechanical response of polymer matrix composites - Jain, D.; Mukherjee, Abhijit; Kwatra, N. (Elsevier Ltd, 2015)
Diffusion of moisture through fibre reinforced polymers (FRP) is one of the main environmental causes of their deterioration and loss of service life. Moisture diffusion and the resulting stresses in a fibre-matrix system vary considerably with the topology of the fibres inside the polymer matrix. This paper reports a numerical study on stress build up in FRP due to moisture diffusion. The Fickian diffusion model is implemented. Stresses due to the transient moisture distribution have been estimated using a finite element model. Some fundamental topologies have been studied. Most important topological parameters have been identified. Utilising the results of fibre neighbourhood, interpretation of large microstructures has been discussed. Considerable interactions among neighbouring fibres can be observed in the stress build up. The results should help in designing moisture impeding microstructures for FRP and prolong their life.